StEFI. Studies of Erudition and Italian Philology (Prassi Ecdotiche della Modernità Letteraria, 2017)
The well-known program of the «Giornale storico della letteratura italiana» promoted the examination of many documents saved in libraries and archives, and the studies of the relationships between European literatures. Times have certainly changed since that program was written; much has been done, but that same program can still be a guide to those who look at Italian Literature and Culture in a perspective of “integral Philology”.